Sistem Informasi Promosi Wisata Desa Pada Eweta Berbasis Web Dengan CodeIgniter - Robertus Umbu Zogara; Cecilia Dai Payon Binti Gabriel; Dian Fransiska Ledi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to design and develop a web-based Eweta Village Tourism Promotion Information System using the Codeigniter Framework to facilitate the dissemination of information on village tourist destinations to the community and tourists. Lokomboro Village has natural and cultural tourism potential that has not been optimally managed, especially in terms of digital promotion. This system was built using the Waterfall software development method, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. This web-based system is equipped with features such as tourist attraction information, photo galleries, tourism activity schedules, and contact details for managers. The CodeIgniter Framework was chosen for its advantages in MVC structure, which facilitates code management, security, and application scalability. Testing results show that the system is capable of displaying promotional information interactively, responsively, and accessible at any time by interested users, making it suitable for use as a tourism promotion medium for Pada Eweta Village.